Review on Melanin Application as an Antibacterial and Antioxidant Agent in Food Packaging - Mustakim, Zainal; Prasetya, Agus; Wintoko, Joko; Kayati, Fitri Nur; Purnomo, Chandra Wahyu (Universitas Gadjah Mada, 2024)
One of the solutions to reduce food waste is creating innovative food packaging to lengthen its shelf life. This type of packaging can be produced by incorporating natural antimicrobials and antioxidation agents such as melanin. Various biologically active and multifunctional properties are associated with this biomacromolecule, i.e., antioxidants, antibacterial properties, and free radical scavengers. Thus, melanin is an indispensable component. It is expected that food packaging manufactured from natural materials containing melanin will have several advantages, including biodegradability, antioxidant ability, and antibacterial activity. A review of melanin as an antibacterial and antioxidant agent from many different sources that is utilized as an additive in food packaging is presented.